Yseut et Tristan comme parents : le Roman d’Ysaÿe le Triste / Yseut and Tristan as Parents : the Romance of Ysaÿe le Triste - Brînduşa Grigoriu (Anastasis: Research in Medieval Culture and Art, 2018)
When a rumor concerning the hero’s parents has the chance to become a medieval romance, the prequel is just as important, in its affective dimension and moral connotations, as the story itself. The present article explores the intertextual creation of a new topos in early modern literature – the fertility brought about by the mythical love potion, in the narrative worlds of Tristan and Ysolt – and the axiological negotiations meant to ensure its reception in the autumn of Arthurian romance.